Efektifitas Pelatihan High Alert Medication Terhadap Pengetahuan dan Sikap Petugas di RS KIA PKU Muhammadiyah Kotagede - Irni Sofiani (Universitas Muhammadiyah Yogyakarta, 2016)
RSKIA PKU Muhammadiyah Kotagede Hospital Type C Special, that in order to maintain the quality and safety of hospital patients, especially the handling of High Alert Medication and prepare for the accreditation of the 2012 version, then RSKIA PKU Muh Kotagede working to improve implementation one of that the Goals Patient Safety with training. Occurrence data and research in pharmaceutical care, as well as general data risk high incidence of errors in the pharmaceutical field especially high alert medications make it a priority to take precedence understanding for officers and implemented. This type of research is descriptive research using a type of mixture (mixed methodology), with a quasi-experimental. The study population were hospital health workers, the sampling technique by purposive sampling. Test analysis using descriptive statistics and qualitatively by comparing with the results of observation, interviews and document research. Test Results Kolmogorov Smirnov normality assumption both knowledge and attitude variables to pre-test and post test both normal distribution. Results Paired Samples Test A (Knowledge) note that t is -6.672 with a significance value of 0.000. Hence the significance of 0.000 <0.05, then Ho is rejected, it means that there is a difference between the average variable knowledge of pre-test and post test. Paired Samples Test / T-test B (attitude), it is known that t is -2.932 with a significance value of 0,010. Hence the significance of 0.010 <0.05, then Ho is rejected, it means that there is a difference between the average variable attitude of pre-test and post test. From interviews with respondents felt more knowledgeable and increase in knowledge after the training given. From the aspect of attitude because respondents feel more knowledgeable after being given training, it leads to a positive attitude in handling the implementation of High Alert Medication. There were changes in knowledge to healthcare workers at RSKIA PKU Muhammadiyah Kotagede after training on High Alert Medication. There is a change in attitude to healthcare workers at RSKIA PKU Muhammadiyah Kotagede after training on High Alert Medication.